1997
DOI: 10.1080/13625189709049933
|View full text |Cite
|
Sign up to set email alerts
|

The effects of monophasic and triphasic oral contraceptives on ovarian function and endometrial thickness

Abstract: All preparations demonstrated profound suppression of ovarian activity and effectively prevented ovulation. Ovarian suppression with desogestrel/ethinylestradiol 150/20 did not differ from that of other OCs despite its lower ethinylestradiol content. The use of both triphasic OCs, having a relatively low progestogenic activity, was associated with a higher ovarian activity than that of the monophasic OCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 19 publications
2
14
0
3
Order By: Relevance
“…The different OCs used is the main cause of day 2 data difference. Rabe et al reported the same finding and attributed this to a relatively low progestogenic activity in the triphastic OCs than that in the monophastic OCs [9]. As elevated LH level in the stage of follicle recruitment is supposed to have negative influence on the quality of oocyte [10].…”
Section: Discussionsupporting
confidence: 53%
“…The different OCs used is the main cause of day 2 data difference. Rabe et al reported the same finding and attributed this to a relatively low progestogenic activity in the triphastic OCs than that in the monophastic OCs [9]. As elevated LH level in the stage of follicle recruitment is supposed to have negative influence on the quality of oocyte [10].…”
Section: Discussionsupporting
confidence: 53%
“…A number of studies either did not assess progesterone levels, 26 had no predefined definition of ovulation, 19,22,25,29,31 or did not perform measurements during the most critical days for escape ovulation. 17,25,27,28,35 COCs containing 15-20 µ µg EE Table 2 shows the studies that have been conducted with COCs containing 15-20 µg EE. 17,23,24,26,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Overall, 12 out of 1030 (1.1%) subjects were found to have ovulated.…”
Section: Cocs Containing 30-35 µ µG Eementioning
confidence: 99%
“…52 Finally, several studies did not measure progesterone at all and relied solely on ultrasound 24,26 whilst others did not predefine the progesterone level indicative of ovulation 46,48,49,52 or did not perform measurements during the critical days for escape ovulation. 17,[40][41][42]51,54 Phasic COCs Table 3 shows the studies performed with triphasic (Tri) or biphasic (Bi) COCs. 8,17,18,23,28,32,33,42,43,49,[56][57][58][59][60][61][62][63] Overall, 21 out of 460 (4.6%) subjects were found to have ovulated.…”
Section: 0mentioning
confidence: 99%
“…Au cours de l'intervalle libre, les taux de FSH et d'oestradiol remontent fortement et le blocage ovarien n'est optimal qu'au bout de sept jours de prise du contraceptif [27,28]. Les follicules qui se développent au cours de l'intervalle libre commencent à régresser après une semaine de prise régulière en raison de la suppression de la sécrétion de FSH [29]. Néanmoins, ils peuvent occasionnellement persister malgré la prise régulière de sept comprimés ou plus [26].…”
Section: éChecs De La Contraception Oraleunclassified